DEVELOPMENT AND VALIDATION OF INSTRUMENT TO MEASURE THE CHARACTERISTICS OF A HEALTHY ROLE-MODEL IN MEDICAL SCHOOL - Michael Andreas Leman; Mora Claramita; Gandes Retno Rahayu (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: A medical teacher as a healthy role-model has a critical role in supporting health promotion effectiveness in medical school. However, an instrument to measure the characteristics of the medical teacher as a healthy role-models is unavailable. This study aimed to develop and validate a questionnaire to evaluate these characteristics by analyzing a model from previous grounded theory.Methods: A total of 442 medical teachers at the Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta, were invited to participate. We used hierarchical component models (HCMs) to develop our path model. A partial least squares structural equation modeling (PLS-SEM) were then used to analyze this model.Results: Twenty-six items from seven constructs supports our model. The construct of socially healthy (SH) has the most substantial effect on constructing healthy people's characteristics (H). The constructs of healthy role-models (HRM) in medical schools are mainly influenced by healthy people characteristic (H).Conclusion: A questionnaire with 26 items grouped in these seven constructs showed good reliability and validity. Seven constructs have relevance to the characteristics of a healthy role-model in the medical school model.